Monetary Policy Transparency and Financial Market Forecasts in South Africa - Arora, Vivek (IMF Working Papers; Working Paper, 2007)
The transparency of monetary policy in South Africa has increased substantially since the end of the 1990s; but little empirical work has been done to examine the economic benefits of the increased transparency. This paper shows that, in recent years, South African private sector forecasters have become better able to forecast interest rates, are less surprised by reserve bank policy announcements, and are less diverse in the cross-sectional variety of their interest rate forecasts. In addition, there is some evidence that the accuracy of inflation forecasts has increased. The improvements in interest rate and inflation forecasts have exceeded those in real output forecasts, suggesting that increases in reserve bank transparency are likely to have played a role.